(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2022)
Different nations got impacted as far as economic and different misfortunes and the extent ofeffect relied upon the prior monetary game plan of the nation and different variables. Because of thisepisode, healthcare sector was one of the most awful impacted. Likewise, it required most venture andneeded to answer rapidly and actually to deal with this emergency. Among the nations impacted, India-amonetary focus with huge overall network was affected straightforwardly, prompting a fast approachingbreakdown of economical business sectors. The purpose of this study is to have a better understandingof the many aspects of economic issues faced by the Indian healthcare system. Specifically, it examinesthe immediate and potential long-term impact of this pandemic on the Indian medical services sector interms of productivity and value.